From monocontextual to multicontextual transfer: Organizational determinants of the intention to transfer generic information literacy competences to multiple contexts - Testers, Laurent; Gegenfurtner, Andreas; Geel, Rolf van; Brand-Gruwel, Saskia (Frontline Learning Research, 2019)
An important goal of educational designers is to achieve long-term transfer of learning that is the learner’s application of newly acquired competencies. Extensive research during more than a century shows that especially in formal educational settings this fundamental aspect of education often occurs poorly or not at all, leading to what is called a Transfer Problem. To address this transfer problem, the present study examines intentions to transfer learning to multiple contexts; this focus on multiple transfer contexts extends previous research focusing on a single transfer context, typically the workplace. The present study aimed to estimate the influence of five organizational variables (peer support, supervisor support, opportunity to use, openness to change, and feedback) on transfer intention in two different transfer contexts: study and work. Participants were 303 students at an open university attending a course in information literacy. The model was tested using structural equation modelling. The results indicated that before starting the course supervisor support and feedback were considered the strongest predictors of intention to transfer new learning in both the study and the work contexts. This research is amongst the first in the training literature to address multi-contextuality and examines intentions to transfer generic competences to the two transfer contexts study and work within one single study.